2021
DOI: 10.1002/jcp.30415
|View full text |Cite
|
Sign up to set email alerts
|

Identification of YAP1 as a novel downstream effector of the FGF2/STAT3 pathway in the pathogenesis of renal tubulointerstitial fibrosis

Abstract: Chronic kidney disease is a global health problem and eventually develops into an end-stage renal disease (ESRD). It is now widely believed that renal tubulointerstitial fibrosis (TIF) plays an important role in the progression of ESRD. Renal tubular epithelial-mesenchymal transition (EMT) is an important cause of TIF. Studies have shown that FGF2 is highly expressed in fibrotic renal tissue, although the mechanism remains unclear. We found that FGF2 can activate STAT3 and induce EMT in renal tubular epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In the past, DKD has been regarded as a disease mainly characterized by glomerular injury, and the role of renal tubular injury in DKD has been neglected; in recent years, more and more studies have revealed the importance of renal tubulointerstitial injury in the progression of DKD [15]. The main cause of tubulointerstitial fibrosis is renal tubular EMT [16,17]; therefore, the inhibition of EMT can alleviate tubulointerstitial fibrosis [18]. EMT is a collective name for a series of cellular biological process in which cells differentiate from epithelial cell phenotype into mesenchymal cells phenotype under specific physiological or pathological conditions [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, DKD has been regarded as a disease mainly characterized by glomerular injury, and the role of renal tubular injury in DKD has been neglected; in recent years, more and more studies have revealed the importance of renal tubulointerstitial injury in the progression of DKD [15]. The main cause of tubulointerstitial fibrosis is renal tubular EMT [16,17]; therefore, the inhibition of EMT can alleviate tubulointerstitial fibrosis [18]. EMT is a collective name for a series of cellular biological process in which cells differentiate from epithelial cell phenotype into mesenchymal cells phenotype under specific physiological or pathological conditions [19].…”
Section: Discussionmentioning
confidence: 99%
“…found that activation of both the EGFR/PI3K/Akt signaling pathway and the RhoA/Rock signaling pathway in diabetic renal proximal tubular epithelial cells promoted YAP activation and there was a crosstalk between these two signaling pathways. In addition to these signaling pathways, both FGF2/STAT3 and YTH domain‐containing protein family (YTHDF1) can also exacerbate renal fibrosis by upregulating YAP expression 307,308 . In conclusion, there are many YAP/TAZ signaling pathways involved in renal fibrosis, so exploring drugs that inhibit the activation of profibrotic YAP/TAZ signaling pathways may open the way for antifibrotic therapy.…”
Section: Yap/taz and Fibrosismentioning
confidence: 99%
“…In addition to these signaling pathways, both FGF2/STAT3 and YTH domain‐containing protein family (YTHDF1) can also exacerbate renal fibrosis by upregulating YAP expression. 307 , 308 In conclusion, there are many YAP/TAZ signaling pathways involved in renal fibrosis, so exploring drugs that inhibit the activation of profibrotic YAP/TAZ signaling pathways may open the way for antifibrotic therapy.…”
Section: Yap/taz and Fibrosismentioning
confidence: 99%
“…Studies have shown that p-STaT1 and p-STaT3 are involved in EMT and subsequent TIF under several conditions (10)(11)(12)(13). The role of STaT3 in eMT and fibrosis has been widely recognized (14)(15)(16)(17)(18); however, other studies have suggested that the activation of STAT1 exhibits anti-fibrotic properties by reducing macrophage infiltration or changing the phenotype of macrophages in renal ischemia-reperfusion injury (19). Tumor-related studies have also demonstrated that the activation of STaT1 mediated the effect of interleukin-27 in reversing trophoblast cell eMT (20).…”
Section: Introductionmentioning
confidence: 99%